The Reliability of Measuring the Inter-recti Distance Using High-resolution and Low-resolution Ultrasound Imaging Comparing a Novice to an Experienced Sonographer - Iwan, T; Garton, B; Ellis, R (Physiotherapy New Zealand, 2014)
Diastasis recti abdominis is an increase in inter-recti distance. This commonly occurs in women postpartum and may lead to weakness and dysfunction of the abdominal muscles. Ultrasound imaging has been previously used to quantify the inter-recti distance. The aims of this study were: 1) to examine the reliability of an experienced versus a novice sonographer in the measurement of inter-recti distance; 2) to examine the reliability of using high-resolution versus low-resolution ultrasound imaging in the measurement of inter-recti distance. Ultrasound measures of the inter-recti distance were recorded in thirty healthy participants at rest and during an abdominal contraction by both an experienced and novice sonographer. Intra-rater, within-session measurement of inter-recti distance demonstrated good to very good reliability. Intra-rater, between session reliability remained very good for the experienced sonographer but declined for the novice sonographer. Results demonstrated excellent agreement between both low and high-resolution ultrasound imaging with no statistically significant differences recorded. There were no statistical differences between the novice and experienced sonographers’ measurements. The results of this study indicate the potential of low-resolution ultrasound imaging to be implemented clinically in the future.
Keywords: Ultrasound imaging; Inter-recti distance; Diastasis recti abdominis; Reliability